Towards high performance Cd-free CZTSe solar cells with a ZnS(O, OH) buffer layer: the influence of thiourea concentration on chemical bath deposition. (23rd February 2016) - Neuschitzer, Markus; Lienau, Karla; Guc, Maxim; Barrio, Lorenzo Calvo; Haass, Stefan; Prieto, Jose Marquez; Sanchez, Yudania; Espindola-Rodriguez, Moises; Romanyuk, Yaroslav; Perez-Rodriguez, Alejandro; Izquierdo-Roca, Victor; Saucedo, Edgardo
Abstract: High-performance kesterite- (CZTSe-)based solar cell devices usually employ an absorber/buffer heterostructure using toxic CdS deposited by chemical bath deposition (CBD) as a buffer layer. This is due to the favourable spike-like conduction band alignment of the CdS buffer and CZTSe absorber. ZnS(O, OH) buffer layers provide a promising nontoxic alternative. Here, variation of the thiourea concentration in the CBD of ZnS(O, OH) buffer layers and its influence on device performances of pure selenide CZTSe heterostructure solar cells is presented. Furthermore, the influence of buffer layer deposition conditions on light-induced metastabilities is discussed. A ZnS(O, OH) buffer layer deposited with a high thiourea concentration leads to distorted illuminated J–V curves as expected for devices with unfavourably high spike-like conduction band alignment between the buffer and CZTSe absorber. By adjusting the thiourea concentration J – V curve distortions can be reduced. An optimized CBD process leads to a device efficiency of up to 6.5% after light soaking, which is comparable to the efficiency of a reference device that employs CdS as the buffer layer (6.9%).